Therapeutic hypothermia for out-of-hospital cardiac arrest: implementation in a district general hospital emergency department. Issue 11 (23rd December 2010) - Patil, Shashank; Bhayani, Sadiq; Denton, John M; Nolan, Jerry
Abstract : Background: The use of therapeutic hypothermia is recommended for unconscious adult patients with return of spontaneous circulation (ROSC) after out-of-hospital ventricular fibrillation cardiac arrest. There is evidence that the time taken to achieve target temperature impacts survival. Objectives: To audit the performance of an emergency department (ED) in implementing therapeutic hypothermia and achieving target temperature in survivors of out-of-hospital cardiac arrest admitted to the intensive care unit (ICU). Methods: Data were extracted from the medical records of patients admitted to the ICU from the ED in the Royal United Hospital following out-of-hospital cardiac arrest (OHCA) between June 2002 and October 2008. The intervals between ROSC and initiation of cooling and between initiation of cooling and achieving the core temperature of 34°C were recorded. Results: During this period, 83 patients were admitted to the ICU following OHCA. Of these, 67 (81%) were actively cooled. All 16 patients who were not cooled had recognised exclusion criteria. The median time (IQR) from ROSC to initiation of cooling was 60 (40–165) minutes and the median time (IQR) to reach 34°C was 175 (40–420) minutes. Of the 67 who were cooled, 44 (66%) achieved the temperature of 34°C within 4 h, the audit standard published by the Royal College of Anaesthetists. In 29 (43%) patients, the temperature increased after leaving the ED. Conclusions: Among OHCA patients who met recognised inclusion criteria, therapeutic hypothermia was implemented successfully by the ED staff. The temperature should be measured continuously from the same site in both the ED and the ICU. This will provide consistent and continuous temperature monitoring between the ED and the ICU and will enable prompt intervention to prevent temperature increases.